In-Hospital Mortality in Patients with Corrosive Ingestion at A Tertiary Care Hospital - Raza, Muhammad; Tariq, Ayesha; Mukhtar, Muhammad; Raza, Ali (Biological and Clinical Sciences Research Journal, 2025)
Corrosive substance ingestion is a critical medical emergency that can lead to serious complications, including in-hospital mortality. The clinical outcomes often depend on the intent of ingestion, socioeconomic factors, and timely management. In developing countries, the burden of corrosive intake-related morbidity and mortality remains significant, yet underreported. Objective: To evaluate the frequency of in-hospital mortality among patients with corrosive ingestion at a tertiary care hospital in Pakistan. Methods: This descriptive case-series study was conducted at the Department of Thoracic Surgery, Nishtar Hospital, Multan, from June 4, 2023, to June 3, 2024. A total of 276 patients hospitalised with corrosive ingestion were enrolled using non-probability consecutive sampling. Patients were followed from admission until discharge to determine in-hospital mortality. A structured proforma was used to collect data on demographics (age, gender, marital status, residential status, education), socioeconomic status, and cause of ingestion (accidental, suicidal, or homicidal). Statistical analysis was performed using SPSS version 25.0. The Chi-square test was applied to determine associations, with a 95% confidence interval and p-value <0.05 considered statistically significant. Results: Out of 276 patients, 117 (42.4%) were male and 159 (57.6%) were female. The most common cause of ingestion was suicidal (87.0%), followed by accidental (10.5%) and homicidal (2.5%). In-hospital mortality was recorded in 19 patients (6.9%). A statistically significant association was observed between socioeconomic status and mortality, with 73.7% of deaths occurring in the low-income group and 22.3% in the lower-middle-income group (p = 0.003). Mortality was noted in 15.8% of accidental cases, 68.4% of suicidal cases, and 15.8% of homicidal instances, though this association was not statistically significant (p = 0.618). Conclusion: Although the overall in-hospital mortality rate from corrosive ingestion was not exceedingly high, it was significantly associated with lower socioeconomic status. Effective and timely management, multidisciplinary care, and psychological intervention remain essential to improve clinical outcomes in these patients.